2015
DOI: 10.1089/dia.2014.0190
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Metformin for Patients with Type 1 Diabetes Mellitus: A Meta-Analysis

Abstract: Metformin may decrease the daily insulin dosage, body weight, and lipid levels in T1DM. However, metformin does not increase the incidence of hypoglycemia and ketoacidosis. High-quality, large-sample, and long-term follow-up clinical trials are needed to confirm these conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0
9

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 30 publications
3
43
0
9
Order By: Relevance
“…Our findings highlight the importance of obesity prevention for all youth and the need for more aggressive measures to prevent CVD in adulthood. Ongoing clinical trials with metformin on obese youth with T1D may improve CVD risk factors that are related to insulin resistance [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings highlight the importance of obesity prevention for all youth and the need for more aggressive measures to prevent CVD in adulthood. Ongoing clinical trials with metformin on obese youth with T1D may improve CVD risk factors that are related to insulin resistance [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as in other studies, we were unable to separate DM by type (Type 1 or Type 2), as this information was missing for 33.3% of cases and 25.8% of controls. Although metformin is mostly used in Type 2 DM, metformin use in individuals with Type 1 DM has increased in recent years, as it may lead to contribute to a decrease in the daily dose of insulin [26]. In present study, metformin was used by five (27.8%) of the 18 participants with Type 1 DM.…”
Section: Discussionmentioning
confidence: 70%
“…15 The authors concluded that metformin (maximum daily dose 1.7g to 2.55g) was not associated with lower HbA 1c levels (267 participants, six studies). However, they did report lower daily insulin dosage (SMD -1.36, 95% CI −2.28 to −0.45; four studies, 241 participants), reduced body weight (mean difference [MD] −2.4kg, 95%CI −4.2 to −0.7; four studies, 178 participants), and lower low-density lipoprotein levels (MD −0.24mmol/L, 95% CI −0.41 to −0.07; three studies, 140 participants) compared with placebo.…”
Section: About Metforminmentioning
confidence: 99%